KEBIJAKAN PELAYANAN DALAM RUMAH BAGI LANJUT USIA DI JEPANG: PELAJARAN UNTUK INDONESIA - Mu'man Nuryana (Politeknik Kesejahteraan Sosial, 2003)
In-Home Service for the Aged in Japan : Lessons Learned for Indonesia.This article examines the social and economic forces that led Japan to create the Gold Plan a comprehensive national plan for formalized in-home services for the aged. Under this national policy, Japan has changed their paradigm on delivery of social services for the aged which the following: shifts from institutional to in-home service workers. Local community and societal at large were encouraged to take part in this regard where new nonprofit organization called Resident-Participation Type (RPT) are growing significantly. PRTs are self-help organizationsto augment the delivery of in-home services to the aged. The current status of these new models for the aged are examined by using secondary data from the surveys conducted by the Japanese National Council of Social Welfare in 1992 and 1993. The future issues regarding RTPs and inhome services for the aged in Japan are discussed in this article with the aim at searching appropriate strategy to deliver social services for the aged in Indonesia.Kata Kunci: In-Home services, Resident-Participation Type, Golden plan, Welfare policy